Contract farming in Mozambique: Implications on gender inequalities within and across rural households - Cecilia Navarra (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper analyses the implication of contract farming on gender inequalities in rural Mozambique. Contract farming is often considered one of the major tools of agribusiness development: it broadly includes those arrangements under which producers commit to provide a pre-defined quantity of crop to a buyer firm. This paper exploits a panel dataset (2002-05) collected by the Mozambican Ministry of Agriculture among a nationally representative sample of rural households to explore contracts' implications for gender equality, both across and within households. We look both at the participation of female-headed households in contracts, and at the impact of establishing a contract on a set of intra-household women empowerment indicators. Concerning the first, our results confirm a selection out of contracts in rural households where a woman is the household's head. With regard to the second, we may expect contrasting effects to be at work: on the one hand, the consequences of increased income relaxing the budget constraint, while, on the other, the effects of an intra-household shift towards men's control over assets. We find different results according to the indicator used: after controlling for selection bias, we find no effect on control over land, but a negative effect on women's access to extension services.
Keywords: O13; J16; C21; C23; 330; contract farming; gender inequalities; women empowerment; Mozambique; propensity score matching